A Comprehensive Overview on Pathogenesis and Management of Osteoarthritis vis-a-vis Sandhigatavāta (International Journal of Ayurveda and Pharma Research, 2022)
The most common joint condition encountered in clinical practice is osteoarthritis (OA) of the knee, which is a primary source of impairment in the elderly. It is a multifactorial chronic degenerative condition characterised by loss of articular cartilage, enlargement of bone at the borders, subchondral sclerosis, and a variety of biochemical and morphological changes to the synovial membrane and joint capsule. OA clinically similar to Sandhigatavāta of Ayurveda is one of the eighty types of Nānātmaja Vātavyādhi. The aetiopathogenesis, symptoms, and treatment of Sandhigatavāta found in a very concise format in classical texts. The authors have tried to put an emphasis on OA related to its prevalence, aetiology and pathogenesis based on Sadkriyākāla along with management by incorporating the knowledge of literary and data base resources in order to establish a guideline for the rational use of treatment modalities. The present approach may be useful for clinicians and researchers to plan appropriate strategy of management and research in the field of OA